Glimepiride and glibenclamide have comparable efficacy in treating acute ischemic stroke in mice. (1st January 2020) - Wang, Xiaoqiang; Chang, Yuan; He, Yihua; Lyu, Chenfei; Li, Hua; Zhu, Juan; Liu, Kewei; Hu, Yafang; Huang, Kaibin; Pan, Suyue
Abstract: Glibenclamide protects against ischemic injury in both preclinical and clinical studies, presumably by blocking the de novo assembled sulfonylurea receptor 1-transient receptor potential M4 (Sur1-Trpm4) channel induced by ischemia. However, glibenclamide may cause unexpected serious hypoglycemia. Here, we tested whether glimepiride, another sulfonylurea with better safety, has comparable efficacy with glibenclamide and whether gene deletion of Trpm4 ( Trpm4 −/− ) exerts similar effect. Wild-type (WT) mice subjected to temporary middle cerebral artery occlusion (tMCAO) were randomized to receive glibenclamide (an initial dose of 10 μg/kg and additional doses of 1.2 μg every 8 h), three different doses of glimepiride (10 μg/kg, 100 μg/kg and 1 mg/kg) or vehicle after ischemia, while tMCAO-treated Trpm4 −/− mice were randomized to receive vehicle or glimepiride. Neurological function, infarct volume, edema formation, the integrity of blood-brain barrier and inflammatory reaction were evaluated at 24 h after ischemia. In tMCAO-treated WT mice, 10 μg/kg and 100 μg/kg glimepiride had comparable efficacy with glibenclamide in improving longa score and grip test score, reducing infarct volume, mitigating brain edema, lessening extravasation of Evans blue dye and IgG, restoring tight junction protein expression as well as suppressing inflammatory cytokines. Compared with WT mice, Trpm4 −/− mice showed less neurological deficit, smaller cerebral infarction, lighter brain edema and more integrity of blood-brain barrier. As expected, glimepiride did not provide additional neuroprotection compared with vehicle in the tMCAO-treated Trpm4 −/− mice. Glimepiride shows comparable efficacy with glibenclamide in alleviating brain injury after ischemic stroke in mice, possibly via targeting the Sur1-Trpm4 channel. Highlights: Glimepiride is safer than glibenclamide, especially in serious hypoglycemia. Glimepiride was similar to glibenclamide in protecting against ischemic stroke. Neurological function and blood-brain barrier were protected. Infarct volume, cerebral edema and inflammatory reaction were lightened. Gene deletion of Trpm4 protected against ischemic stroke.